Low Mutational Burden of Eight Genes Involved in the MAPK/ERK, PI3K/AKT, and GNAQ/11 Pathways in Female Genital Tract Primary Melanomas. (28th January 2015) - Pappa, Kalliopi I.; Vlachos, George D.; Roubelakis, Maria; Vlachos, Dimitrios-Efthymios G.; Kalafati, Theodora G.; Loutradis, Dimitrios; Anagnou, Nicholas P.
Abstract : Mucosal melanomas exhibit discrete genetic features compared to cutaneous melanoma. Limited studies on gynecological melanomas revealed significant heterogeneity and low mutational burden. To gain further insight into their genetics and DNA repair efficiency, we systematically investigated the status of eight genes whose products are critically involved in the MAPK/ERK, PI3K/AKT, and GNAQ/11 pathways, including BRAF, NRAS, HRAS, KRAS, c-KIT, PI3K, GNAQ, and GNA11, in a series of 16 primary gynecological melanomas, covering all anatomical locations, ranging from stages I to III. Analysis either by real-time PCR coupled with fluorescence melting curve analysis or by PCR followed by direct sequencing, along with studies for DNA mismatch repair status using immunohistochemistry, disclosed that 15 out of the 16 cases displayed wild-type genotypes, with a single case of vulvar primary melanoma, harboring the activating mutation BRAF V600E . Investigations on whether this could reflect partly an efficient mismatch repair (MMR) mechanism were confirmed by normal expression of hMLH1 and hMSH2, suggesting that the lack of mutations could be explained by the operation of alternative pathogenetic mechanisms modulating downstream effectors of the signaling pathways. Our data suggest the presence of additional genetic components and provide the impetus for systematic approaches to reveal these yet unidentified genetic parameters.